Proceedings of the 17th International Conference on Cognition and Exploratory Learning in the Digital Age (CELDA 2020) 2020
DOI: 10.33965/celda2020_202014l038
|View full text |Cite
|
Sign up to set email alerts
|

Factors of the Use of Learning Analytics Dashboard That Affect Metacognition

Abstract: In this study, we used a learning analytics dashboard (LAD) in a higher education course to support students' metacognition and evaluated the effects of its use. The LAD displays students' reading path and specific behaviors when viewing digital learning materials. The study was conducted on 53 university students to identify the factors that affected metacognition changes in terms of their awareness and behavior dimensions when using the LAD. In terms of results, first, the students' perception of visual attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…A reduced dropout rate from an LA intervention results in fewer learners failing to finish coursework (e.g., Cambruzzi et al, 2015). Other positive effects can also include better engagement with a course (Chen et al, 2020), usage of learning management system (LMS) resources (e.g., Jovanović et al, 2021), and eventually improved course grades (e.g., Wong, 2017). Finally, the outcome from a LA intervention can be seen in form of enhanced SRL processes (e.g., Roll & Winne, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…A reduced dropout rate from an LA intervention results in fewer learners failing to finish coursework (e.g., Cambruzzi et al, 2015). Other positive effects can also include better engagement with a course (Chen et al, 2020), usage of learning management system (LMS) resources (e.g., Jovanović et al, 2021), and eventually improved course grades (e.g., Wong, 2017). Finally, the outcome from a LA intervention can be seen in form of enhanced SRL processes (e.g., Roll & Winne, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Due to the advantages of e-books, such as flexibility of content design and Internet accessibility (Yamada et al, 2017), their application in university settings has been rapidly growing Chen et al, 2020;Shimada et al, 2019;Zarzour et al, 2020).…”
Section: Literature Review E-book Systems In High School Educationmentioning
confidence: 99%
“…Learning strategies used by students are often related to learning performance during independent study and lectures (Chen et al, 2020). Broadbent and Poon (2015) revealed that SRL strategies were significantly correlated with online learning performance.…”
Section: Learning Analytics For E-book Learning Behaviorsmentioning
confidence: 99%
“…LA Interventions that promote a better retention rate improve the learner's continuous study in a course (e.g.,Freitas et al, 2015), whereas LA interventions that create greater completion rates re ect learners' successful completion of individual courses and thesis processes (e.g.,Nouri et al, 2019).A reduced dropout rate from an LA intervention results in fewer learners failing to nish coursework (e.g.,Cambruzzi et al, 2015). Other positive effects can also include better engagement with a course(Chen et al, 2020), usage of learning management system (LMS) resources (e.g.,Jovanović et al, 2021), and eventually improved course grades (e.g., B. T. M Wong, 2017)…”
mentioning
confidence: 99%